Effectiveness and Safety of Treating Negative Emotions after PCI from the Perspective of Qi and Blood: A Systematic Review and Meta-Analysis. (8th September 2022) - Liu, Fang; Liu, Fuming; Li, Jia; Du, Yuying; Han, Xu
Abstract : Aim of the Study . This study aimed to systematically evaluate the effectiveness and safety of treating negative emotions after percutaneous coronary intervention (PCI) based on the theory of "harmonization of qi and blood." Background . Many patients undergoing PCI have been reported to suffer from psychological distress and negative emotions. Several lines of evidence have indicated that PCI patients with negative emotions are particularly vulnerable to myocardial reperfusion injury when they face psychological challenges. As proven by clinical trials and research, traditional Chinese medicine (TCM) has certain advantages in alleviating psychological symptoms in PCI patients. The level of evidence for TCM is not yet high. There is no existing systematic review to evaluate the effectiveness and safety of TCM in post-PCI patients. Methods . PubMed, EMBASE, Cochrane Library, Web of Science, CNKI, VIP, Wanfang Database, and CBM were searched to identify randomized controlled trials (RCTs) that treated negative emotions after PCI using qi and blood cotherapy. The search period was from database inception to March 1, 2022. After applying the inclusion and exclusion criteria to the RCTs, research quality evaluation and data extraction were conducted, and a meta-analysis of the articles was performed using Revman 5.3 and Stata 12.1. Results . A total of 14 RCTs involving 1314 patients were included. Meta-analysis results indicated that compared with the anti-anxiety and depression medications group, the qi-blood harmony group was more effective in clinical outcomes (RR = 1.19, 95% CI (1.13, 1.25), P < 0.00001 ), maintaining the stability of angina pectoris (SMD = 0.65, 95% CI (0.29, 1.01), P = 0.0004 ), increasing the degree of patients' satisfaction (SMD = 0.95, 95% CI (0.25, 1.65), P = 0.008 ), reducing the frequency of attacks (SMD = 0.64, 95% CI (0.11, 1.18), P = 0.02 ), and the incidence of adverse reactions (RR = 0.54, 95% CI (0.43, 0.68), P < 0.00001 ). The HAMA and HAMD scores were significantly lower after treatment, and there was no significant difference between the two groups (HAMA: RR = 1.03, 95% CI (0.95, 1.12), P = 0.4 ). The efficacy of the two groups was comparable. In terms of reduction of the HAMD score, after sensitivity analysis, the literature by Liang was found to be significantly influencing the results, and after excluding the results of Liang, the qi-blood harmony group was superior to the Western medicine group for reducing the HAMD score (RR = 1.12, 95% CI (1.01, 1.24), P < 0.05 ), which was significantly different. The results of this review, combined with the grade evaluation, suggest that the HAMA posttreatment score reduction, the efficacy of TCM treatment, and the incidence of adverse reactions were supported by moderate evidence, and the HAMD posttreatment score reduction and the SAQ score were supported by low-quality evidence. Conclusion . Treating negative emotions after PCI based on the idea of "harmonization of qi and blood" can effectively improve the clinical efficacy, the stability of angina pectoris and the degree of patient satisfaction, and can reduce the frequency of angina attacks and the incidence of adverse events. There was no significant difference between the two groups for reductions in the HAMA and HAMD scores. However, more high-quality, large sample, multicentre RCTs are still needed for further verification. PROSPERO Registration Number : PROSPERO CRD42022313169 .